THE EFFECT OF CLIENT BUSINESS COMPLEXITY, AUDIT COMMITTEE SIZE, AND AUDITOR SPECIALIZATION ON AUDIT REPORT LAG - Rizky Maulana; Dewi Darmastuti (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This research is a quantitative study that aims to examine the effect of client business complexity, auditor Speialization, and audit committee size on Audit Report Lag. This study uses audited financial report data for energy sector companies listed on the Indonesia Stock Exchange (IDX) for 2018-2020. By using a purposive sampling technique, 75 sample data were obtained from 37 companies in the energy sector. This study uses panel data regression analysis. The results of this study indicate that internal factors such as client business complexity, audit committee size and external factors, namely auditor Spesialization, have no effect on audit report lag. This shows that during the pandemic, the huge decline in profits was the most important problem and these companies were reluctant to convey this bad news. In addition, auditors also need more time to assess the company's going concern during the pandemic. Keywords: Audit Report Lag, Client Business Complexity, Auditor Spesialization,Audit Committee Size, Covid-19 pandemic